Exploring Comorbidities in Adolescent and Young Adults with Hypermobile Ehlers-Danlos Syndrome with and without a Surgical History: A Preliminary Investigation - Haley Gagnon; Claire E. Lunde; Ziyan Wu; Eduardo N. Novais; David Borsook; Christine B. Sieberg (MDPI AG, 2023)
Ehlers-Danlos Syndrome (EDS) is a rare disease affecting the skin, joints, vasculature, and internal organs. Approximately 85% of those affected are categorized as the hypermobile type (hEDS), which is associated with numerous medical and psychiatric comorbidities, including chronic pain. Additionally, approximately 71% of patients with hEDS undergo at least one surgical procedure; however, indicators for surgery and pain outcomes after surgery are poorly understood. This preliminary study used a medical chart review to identify the frequency and nature of comorbidities in a cohort of adolescents and young adult patients with hEDS and a surgical history compared to those without a surgical history. Results showed that patients diagnosed with hEDS who underwent surgery reported significantly more comorbidities (e.g., CRPS, IBS, Fibromyalgia, POTS, hypothyroidism, etc.) than those who did not have surgery. Seventy percent of individuals who presented for surgery fell within the categories of orthopedic, gastrointestinal, or laparoscopic/endometriosis-related surgeries. Identifying patients with hEDS who are at risk for needing surgery will help identify the mechanisms contributing to risk factors for poor surgical outcomes. The results of this study may be instructive in the management and care of hEDS patients undergoing surgery.